Animasi 2D Motion Graphic sebagai Media Edukasi tentang Dampak Kesepian di Era Digital terhadap Kesehatan Mental: Media Edukasi tentang Dampak Kesepian di Era Digital terhadap Kesehatan Mental - Muh Nur Fauzan Fauzan; Evelyne Henny Lukitasari; Ahmad Khoirul Anwar (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2026)
Mental health is a state of individual psychological well-being that influences how they think, feel, behave, and interact with their social environment, particularly in the context of digital technology developments. Loneliness among adolescents in the digital age, driven by social media and other digital platforms, affects their social and emotional well-being. The primary medium for this design is 2D motion graphic animation as an educational tool. Based on observations and a literature review, it was found that the high use of digital media by adolescents and the lack of education about loneliness in the digital age exacerbate the situation. Information that tends to be textual and informative becomes less engaging and harder for adolescents to understand. The increasing incidence of loneliness among adolescents has the potential to impact adolescent mental health, and public awareness of the issue of loneliness in the digital age remains relatively low. The objective of this design is to create a 2D motion graphic animation that conveys an educational message about the negative impacts of loneliness in the digital age, using a visual approach relevant to adolescents' lives. This design offers 2D motion graphic animation media that uses visuals, colors, and movement that are more closely aligned with adolescent consumption habits and can build empathy visually and emotionally. This design utilizes the Design Thinking method, which encompasses the main stages of empathize, define, ideate, and prototype. The resulting design is a 2D motion graphic animation that presents the impact of loneliness in the digital age on the emotional well-being of adolescents. This design is expected to educate the public about loneliness